A ‘norm’ in the Ancient Greek dialectal lexicon? A comparative study of Gregory of Corinth’s Περὶ Αἰολίδος and the anonymous Γλῶσσαι κατὰ πόλεις (Urb. Gr. 157) - Sowa, Wojciech (Lingua Posnaniensis, 2026)
This paper examines how ancient and Byzantine scholars may have conceptualised a “dialectal” lexicon of Greek, with particular attention to the problem of linguistic normativity. It offers a comparative discussion of two markedly different sources: Gregory of Corinth’s Περὶ Αἰολίδος and the anonymous lexicographical compilation Γλῶσσαι κατὰ πόλεις (Urb. Gr. 157). Both works seek to illustrate dialectal variation primarily through lexical material, yet they do so within distinct scholarly frameworks and with differing assumptions about linguistic correctness. The analysis draws on criteria developed in modern Ancient Greek dialectology (notably by García Ramón) in order to assess how far the lexical items presented in these sources can be regarded as genuinely dialect specific. Given the secondary nature of the evidence, these criteria cannot be applied mechanically; rather, they serve as a heuristic tool for evaluating the internal logic and reliability of the lexicographical traditions under consideration. Particular attention is paid to the role of literary language, poetic diction, and interdialectal influence in shaping what ancient scholars classified as “dialectal”. The study shows that Gregory of Corinth operates with an implicit normative baseline, ultimately rooted in Attic and the learned tradition, against which other dialects are evaluated, whereas the Γλῶσσαι κατὰ πόλεις lack any explicit reference to a standard variety and instead reflect classificatory practices derived largely from literary authority. In both cases, dialectal normativity emerges as prescriptive and scholarly rather than descriptive of vernacular usage. The findings underline the difficulty of defining a “dialectal” lexicon for Ancient Greek and suggest that modern lexicographical approaches must take greater account of the literary, chronological, and scholarly filters through which dialectal material has been transmitted.